Use of dietary supplements among physicians at a hospital in Turkey - Çapar, Aslı Gizem; Yılmaz, Müge (Progress in Nutrition, 2019)
Background and aim: This research was carried out as a descriptive study in order to determine the status of dietary supplement and dietary habits of physicians working at Erciyes University Faculty of Medicine. Methods: A total of 370 people, 165 women, and 205 men, were included in the study. Data were collected by face-to-face interview using questionnaire forms. Results: The ratio of physicians using dietary supplements was 7.3%. Use of multivitamin-mineral supplements (51.9%) and daily dietary supplements (40.7%) constituted the majority. Maintaining good health was the primary reason for using the dietary supplement. It was found that dietary supplement use was more common in middle-aged physicians (51.9%) compared to younger physicians (37.0%) (p < 0.05). Those who used dietary supplement consumed more quantities of dairy products and vegetables and fruits compared to those not using the dietary supplement (p< 0.05). Consumption of legumes for 2-3 times a week was higher in participants using dietary supplements (66.7% vs. 44.6%, p = 0.029). In the group using dietary supplements, the daily consumption of dairy products and vegetables-fruits was higher than those who did not use dietary supplements (p < 0.05). Conclusion: As our knowledge, this is the first research determined the using of dietary supplements among physicians in Turkey. Although physicians using dietary supplement were found to have better dietary habits than those who did not use, neither user nor non-user physicians consumed food groups at the recommended frequency and amounts.